Diskursus Hermeneutika sebagai Metode Interpretasi Ruh Teks - Sassi, Komarudin (At-Tahfidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
This study explores the discourse of hermeneutics as a method of interpretation of the "spirit of text". Hermeneutics as a method of interpretation cannot be separated from the three entities involved, namely; world of author, world of text, and world of readers. If one of the three main entities does not occur dialectical-combination and is even far from each other because of the time span, place and culture. As a consequence, the text becomes something foreign to the reader, even though in this case the "spirit of the text". The "spirit text" referred to in this paper is the holy text of religion (al-Qur'an). Based on the "eidetic" analysis, it turns out that there are still pros and cons from experts in the functioning of hermeneutics as a method of interpreting the "spirit of text" especially this is because the "spirit of the text" comes from an entity that is not the same as humans, namely God.